Deletion of the short arm of chromosome No. 10. Issue 1 (March 1975) - Shokeir, M H; Ray, M; Hamerton, J L; Bauder, F; O'Brien, H
Abstract : A newborn male infant, whose karyotype was 46, XY, del(10)(p13) is presented. The clinical features included cleft lip and palate, preauricular pits, low set malpositioned auricles, antimongoloid slant of the eyes, microcephaly, micrognathia, congenital heart disease, hypertrophic pyloric stenosis, cryptorchidism, and abnormal dermatoglyphics. The child died at the age of 3 months in overwhelming urinary infection with septicemic complications. It is suggested that the features described here may represent a new, clinically recognizable chromosomal syndrome.